Increasing Students’ Long-Term Well-Being by Mandatory Intervention – A Positive Psychology Field Study - Skarin, Frida; Wästlund, Erik (Frontiers in Psychology, 2020)
Is it possible to help students experience increased wellbeing that proceeds by volitional actions from mandatory participation in interventions? The aim of this field study was to better understand the influence of expectancy, motivation, and wellbeing experiences during a positive activity intervention on long-term behavior change and long-term wellbeing. The study included 59 students enrolled in a course that included choosing a positive activity that they would plan for and implement in their lives for six weeks. The participants answered questionnaires before (pre-measure) and after the intervention (short-term measure), as well as at an unannounced follow-up questionnaire six months later (long-term measure). Overall, the results indicate the importance of coexisting intrinsic motivation and high expectancy on the outcome, and that the key driver of sustained volitional behavior change and experiencing long-term increased wellbeing is to experience increased wellbeing during the intervention. The results of the study show that it is possible to help students experience increased wellbeing that proceeds by volitional actions. The study shows that a mandatory positive activity intervention, including free choice of activity and course of action, can induce new long-term behaviors and long-term increased wellbeing.